Analisis manajemen risiko pembiayaan syariah dalam menghadapi lonjakan transaksi digital dan perubahan perilaku nasabah - Mayang, Endang (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has transformed the landscape of banking transactions, including in the Islamic finance sector, which has experienced a significant increase in transaction volume. This phenomenon has been accompanied by changes in customer behavior, with customers increasingly relying on digital services, thereby creating new challenges in financing risk management. This study aims to explore the application of Islamic financing risk management in addressing the surge in digital transactions as well as the dynamics of customer behavior. The research method employed is qualitative, utilizing a literature review approach and descriptive analysis of risk management practices in Islamic banking. The findings indicate that the rise in digital transactions introduces new risks, including technology-based operational risks, moral hazard risks, and the potential for an increase in non-performing financing. Therefore, adaptive, technology-based, and integrative risk management strategies are crucial for maintaining operational stability and building customer trust. These findings are expected to contribute to the development of a risk management framework aligned with digital transformation in the Islamic banking sector.